2021
DOI: 10.3390/ncrna7040064
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the RNA Chaperone Hfq on Target mRNAs Promotes the Small RNA RyhB-Induced Degradation in Escherichia coli

Abstract: Many RNA-RNA interactions depend on molecular chaperones to form and remain stable in living cells. A prime example is the RNA chaperone Hfq, which is a critical effector involved in regulatory interactions between small RNAs (sRNAs) and cognate target mRNAs in Enterobacteriaceae. While there is a great deal of in vitro biochemical evidence supporting the model that Hfq enhances rates or affinities of sRNA:mRNA interactions, there is little corroborating in vivo evidence. Here we used in vivo tools including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…These data are consistent with earlier studies, which demonstrated that sRNA-induced efficient cleavage of target mRNAs by RNase E requires both Hfq and a functional RNA degradosome ( 21 , 25 ). Additionally, it was previously shown that target mRNA decay subsequently drives the sequential degradation of the paired sRNAs in certain cases ( 20 , 21 , 24 ). However, the mechanism by which the CTD recognizes Hfq in vivo to initiate RNase E–dependent degradation of the mRNA–sRNA hybrid remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are consistent with earlier studies, which demonstrated that sRNA-induced efficient cleavage of target mRNAs by RNase E requires both Hfq and a functional RNA degradosome ( 21 , 25 ). Additionally, it was previously shown that target mRNA decay subsequently drives the sequential degradation of the paired sRNAs in certain cases ( 20 , 21 , 24 ). However, the mechanism by which the CTD recognizes Hfq in vivo to initiate RNase E–dependent degradation of the mRNA–sRNA hybrid remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the crucial role of the CTD in modulating Hfq-dependent sRNA regulation, the molecular mechanisms underlying the Hfq–sRNA–mRNA complex (Hfq–RNA complex) recognition by RNase E CTD in vivo remain unknown. Indeed, there has been an increasing body of evidence suggesting that association of Hfq with the CTD of RNase E likely occurs in the presence of RNA ( 15 , 22 24 ).…”
mentioning
confidence: 99%
“…Interestingly, all fifteen of the isrR* mutant strains, isolated during two separate screening events, contained the same mutation in the operator of isrR suggesting that there is something unique about this allele. In alternate organisms, small proteins, such as Hfq in E. coli , promote interaction between a sRNA and a target mRNA (49). The finding that suppressor mutations only mapped to the promoter of isrR , and not to alternate loci including hfq , suggest that S. aureus does not require a single protein to facilitate interaction between IsrR and target RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The Hfq protein of E. coli is a relatively small polypeptide composed of 102 amino acid residues (aa), which interacts with different transcripts, in particular small noncoding RNAs, and functions as an RNA chaperone [38,39]. This activity operates predominantly through facilitating RNA-RNA interactions, thus modulating the availability of mRNA molecules to the translation machinery [9].…”
Section: Discussionmentioning
confidence: 99%